Immunohistochemical analysis of caspase expression in the brains of individuals with obesity or overweight - Erick Gómez‐Apo; Juan Silva‐Pereyra; Virgilia Soto‐Abraham; Alejandra Mondragón‐Maya; Javier Sanchez‐Lopez (Obesity Science & Practice, 2023)
Abstract Mechanisms underlying the negative effects of obesity on the brain are still unknown. Obesity is associated with oxidative stress in the brain and neuroinflammation that promotes neurodegenerative diseases. Chronic low‐grade neuroinflammation in obesity could be associated with lower volumes of gray matter and lower neuronal density. If neuroinflammation mediated by the expression of cytokines and chemokines leads to apoptosis, this can be assessed by examining caspase expression. The aim of this study was to compare the expression of caspases in the 16 brains of donors with obesity/overweight (n = 8; Body Mass Index [BMI] = 31.6 ± 4.35 kg/m2; 2 females; Age = 52.9 ± 4.76 years) and normal weight (n = 8; BMI = 21.8 ± 1.5 kg/m2; 3 females; Age = 37.8 ± 19.2 years). Sixteen human brain samples were processed. Serial paraffin sections were examined by anti‐caspase immunochemistry (caspase‐3, caspase‐4, caspase‐6, caspase‐1, caspase‐8, and caspase‐9 antibodies). Postmortem samples of cerebral cortex tissue were captured as photomicrographs and the images obtained were analyzed using ImageJ software to obtain the percentage of positive caspase expression. Nonparametric Mann–Whitney U tests were performed to compare caspase expression between samples from donors with obesity/overweight and normal weight. Taking into consideration the immunohistochemistry results, the Search Tool for the Retrieval of Interacting Genes was used to model molecular interactions. Results showed that brain samples from individuals with obesity/overweight exhibited significantly greater values of positive expression for Caspase‐1 (U = 16.5, p = 0.05, Cohen d = 0.89) and −8 (U = 15, p = 0.03, Cohen d = 0.99) than those from donors with normal weight. This study contributes to the knowledge about the inflammatory effects of obesity/overweight on brain, suggesting the activation of the alternative inflammasome pathway in which interact caspase‐1 and ‐8.